International economic activities and the demand for skilled labor : evidence from Brazil and China - Fajnzylber, Pablo 1964- (Policy research working paper, 2004)
"Increases in international economic integration can lead to greater specialization according to comparative advantage, but also to the diffusion of skill-biased technologies. In developing countries characterized by relative abundance of unskilled labor, these factors can have opposite effects on the relative demand for skilled labor. Fajnzylber and Fernandes investigate the impact of the use of imported inputs, exports, and foreign direct investment on the demand for skilled workers by Brazilian and Chinese manufacturing plants. They find that while in Brazil increased levels of international integration are associated with an increased demand for skilled labor, the opposite is true in China. This paper 'a product of the Growth and Investment Team, Development Research Group' is part of a larger effort in the group to study the links between globalization and labor markets"--World Bank web site